The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep20298
|View full text |Cite
|
Sign up to set email alerts
|

Altered periaqueductal gray resting state functional connectivity in migraine and the modulation effect of treatment

Abstract: The aims of this study were to 1) compare resting state functional connectivity (rs-fc) of the periaqueductal gray (PAG), a key region in the descending pain modulatory system (DPMS) between migraine without aura (MwoA) patients and healthy controls (HC), and 2) investigate how an effective treatment can influence the PAG rs-fc in MwoA patients. One hundred MwoA patients and forty-six matched HC were recruited. Patients were randomized to verum acupuncture, sham acupuncture, and waiting list groups. Resting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
126
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 57 publications
(71 reference statements)
13
126
1
Order By: Relevance
“…Especially, we found that the rsFC was significantly increased between the right iVS-left rMPFC and the left vrP-right AMY/PHC. This result is consistent with previous studies showing the ventral striatum plays an important role in acupuncture treatment (Lee et al, 2015; Li et al, 2016; Pariente, White, Frackowiak, & Lewith, 2005). The rMPFC is an important region dedicated to representing the hedonic properties of reward, focusing on learning appropriate action-reward contingencies, and selecting those actions that potentially lead to reward (Ridderinkhof, van den Wildenberg, Segalowitz, & Carter, 2004).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Especially, we found that the rsFC was significantly increased between the right iVS-left rMPFC and the left vrP-right AMY/PHC. This result is consistent with previous studies showing the ventral striatum plays an important role in acupuncture treatment (Lee et al, 2015; Li et al, 2016; Pariente, White, Frackowiak, & Lewith, 2005). The rMPFC is an important region dedicated to representing the hedonic properties of reward, focusing on learning appropriate action-reward contingencies, and selecting those actions that potentially lead to reward (Ridderinkhof, van den Wildenberg, Segalowitz, & Carter, 2004).…”
Section: Discussionsupporting
confidence: 94%
“…Recently, rsFC has been used to investigate the underlying mechanism of acupuncture in healthy subjects (Bai, Qin, Tian, Dai, & Yang, 2009; Dhond, Yeh, Park, Kettner, & Napadow, 2008; Hui et al, 2009; Liu et al, 2009; Qin et al, 2008; Zhong et al, 2012), and patient populations, such as patients with MDD (Deng et al, 2016; Yi et al, 2012), knee osteoarthritis (Chen et al, 2015; Egorova, Gollub, & Kong, 2015), migraines (Li et al, 2016) and Alzheimer’s disease (Wang et al, 2014). For instance, investigators found that peripheral nerve stimulation and acupuncture can significantly modulate the rsFC of the default mode network (Deng et al, 2016; Fang et al, 2016), amygdala (Liu et al, 2016), and anterior cingulate cortex (Yi et al, 2012) in MDD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies [6, 7] supported that PAG network participated in the migraine, which may impair the descending pain modulatory. In episodic migraine (EM) paitents, it had been detected for the nonspecific PAG lesions on T2WI [8], impaired iron homeostasis of PAG [1], and increased mean kurtosis and mean diffusivity on diffusion kurtosis imaging [9].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies suggested that acupuncture can significantly modulate rsFC in healthy subjects (Bai et al, 2009, Dhond et al, 2008, Hui et al, 2009; P. Liu et al, 2009, Qin et al, 2008, Zhong et al, 2012) and patient populations, such as patients with knee osteoarthritis (X. Chen et al, 2015, Egorova et al, 2015), migraine (Li et al, 2016a, Li et al, 2016b, Li et al, 2016a, Li et al, 2016b, Zhao et al, 2014) and Alzheimer's disease (Z. Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%